'I'd struggle to see it as cheating': the policy and regulatory environments of study drug use at universities. Issue 2 (23rd February 2021) - Dunn, Matthew; Dawson, Phillip; Bearman, Margaret; Tai, Joanna
ABSTRACT: Students use various licit and illicit substances to enhance their academic performance. As yet, no study has explored whether this is an issue of concern for those working in the higher education sector. This study aimed to explore study drug policy, regulatory environments and responses within Australian universities. Semi-structured interviews were conducted with 14 participants from five Australian universities. Nine participants were based in school/department, faculty, or institutional head of teaching and learning roles; six participants were in student support roles. Eight participants had direct teaching experience. Three themes emerged from the data analysis. Study drug use was seen as a health problem rather than a threat to academic integrity. Participants believed that attributes of the university setting may facilitate study drug use, but also considered that some attributes may prevent the uptake of use, such as a stronger emphasis on universities promoting the benefits of a balanced lifestyle.